Clinical outcome of standardized (177)Lu-PSMA-617 therapy in metastatic prostate cancer patients receiving 7400 MBq every 4 weeks - Rasul, Sazan (Eur J Nucl Med Mol Imaging, 2019)
PURPOSE: [(177)Lu]Lu-PSMA-617 radio-ligand therapy (PSMA-RLT) is emerging in patients with an advanced metastatic castration-resistant prostate cancer (mCRPC). Here, we aimed to estimate the results of PSMA-RLT in terms of response, progression-free survival (PFS), and overall survival (OS) in patients receiving a highly standardized treatment regimen due to mCRPC. The toxicity of PSMA-RLT has also been evaluated. PATIENTS AND METHODS: Fifty-four patients (mean age 72 ± 7 years, median PSA at time of initial therapy 66 [range 1.0–4890 μg/L]), receiving three PSMA-RLT cycles (mean 7315 ± 573 MBq) at four weekly intervals, were included in this retrospective analysis. Hematological and biochemical parameters were regularly determined in every patient. Kaplan-Meier estimates were used to assess PFS and OS and a Cox proportional hazard model was used to analyze significant associations. Treatment response was based on PSA measurements 4 weeks after the 3rd treatment. RESULTS: The majority of patients were previously treated with abiraterone/enzalutamide (69%) and docetaxel/cabazitaxel (67%). In total, 79% of the patients showed a decrease in PSA (median PSA decrease from 66 to 19.8, range 0.7–4563 μg/L, P < 0.001) 1 month after the 3rd therapy cycle. Among them, 58% and 35% demonstrated a PSA-decline of > 50% and > 80%, respectively. Median OS was 119 weeks; median PFS was 25 weeks. Patients presenting with a PSA decline had significantly longer PFS (27 vs. 15 weeks, P < 0.0001) and OS (median survival not reached vs. 52 weeks, P < 0.001) than patients with no PSA reduction. Moreover, patients with reduction in PSA levels ≥ 50% (median survival not reached vs. 52 weeks, P < 0.0001) and ≥ 80% (median survival not reached vs. 87 weeks, P = 0.008) lived significantly longer. While hemoglobin did not change during treatment, levels of platelets (236 ± 71 g/L vs. 193 ± 67 g/L) and leucocytes (6.5, range 2.9–13.7 g/L vs. 4.8, range 1.5–12.3 g/L) decreased significantly, both P < 0.001. Two grade 3 leukocytopenia and one grade 3 anemia were observed. CONCLUSION: Intense PSMA-RLT regime with four weekly intervals between the cycles is well-tolerated and offers favorable response rates, PFS, and survival rates for patients with mCRPC.